Improving antibiotic initiation and duration prescribing among nursing home physicians using an audit and feedback intervention: a theory-informed qualitative analysis. Issue 1 (4th February 2021) - Laur, Celia; Sribaskaran, Thivja; Simeoni, Michelle; Desveaux, Laura; Daneman, Nick; Mulhall, Cara; Lam, Jonathan; Ivers, Noah Michael
Abstract : Background: In nursing homes, 25%–75% of antibiotic days of treatment are inappropriate or unnecessary and are often continued for longer durations than necessary. In Ontario, physicians can receive a provincial audit and feedback report that provides individualised, confidential, data about their antibiotic prescribing. Objectives of this study were to explore antibiotic prescribing of nursing home physicians and the influence of the report. Methods: All physicians who received a personalised MyPractice: Long-Term Care report from Ontario Health (Quality) (OH(Q)) in January 2019 (n=361) were eligible to participate in semistructured telephone interviews that were recorded then transcribed verbatim. Recruitment emails were sent from OH(Q) until saturation of ideas. Analysis was conducted by two team members inductively, then deductively using the theoretical domains framework, a comprehensive, theory-informed framework to classify determinants of specific behaviours. Results: Interviews were conducted with n=18 physicians; 78% (n=14) were men, practising for an average of 27 years, with 18 years of experience working in nursing homes. Physicians worked in a median of 2 facilities (range 1–6), with 72% (n=13) in an urban setting. 56% (n=10) were medical directors for at least one home. Professional role and identity impacted all aspects of antibiotic prescribing. Key roles included being an 'Appropriate prescriber', an 'Educator' and a 'Change driver'. For antibiotic initiation, these roles interacted with Knowledge, Skills, Beliefs about consequence, Beliefs about capabilities, and Social influence to determine the resulting prescribing behaviour. When considering the impact of interacting with the report, participants' perceived roles interacted with Reinforcement, Social influence, and Intention. Environmental context and resources was an overarching domain. Conclusion: This theory-informed approach is being used to inform upcoming versions of existing audit and feedback initiatives. Appealing to the role that prescribers see themselves offers a unique opportunity to encourage desired changes, such as providing tools for physicians to be Educators and facilitating, particularly medical directors, to be Change drivers.